Effect of aging and cementation systems on the bond strength to root dentin after fiber post cementation - Nogueira, Caio Henrique de Paula [UNESP]; Gelio, Mariana Bena [UNESP]; Besegato, João Felipe [UNESP]; Ramos, Anna Thereza Peroba Rezende [UNESP]; Fernández, Eduardo; Kuga, Milton Carlos [UNESP]; Saad, José Roberto Cury [UNESP] (FapUNIFESP (SciELO), 2023)
This study evaluated the effect of aging and cementation of fiber posts using glass ionomer and resin cements on push-out bond strength, failure mode, and resin tag formation. One hundred and twenty bovine incisors were used. After post-space preparation, the specimens were randomly allocated into 12 groups (n = 10) according to the cementation system used: GC - GC Gold Label Luting & Lining); RL - RelyX Luting 2; MC - MaxCem Elite; RU - RelyX U200 and the aging periods (24 hours, 6 months, and 12 months). Slices from the cervical, middle, and apical thirds were obtained and analyzed by push-out bond strength test and confocal laser scanning microscopy. One-way ANOVA and Tukey's post-hoc test was used at a significance level of 5%. For the push-out bond strength test, no differences among GC, RU, and MC in the cervical and middle thirds were observed, regardless of the period of storage (P > 0.05). In the apical third, GC and RU showed similar bond strength but higher than other groups (P > 0.05). After 12 months, GC showed the highest bond strength (P < 0.05). Bond strength to post-space dentin decreased over time, regardless of the cementation system used. Cohesive failure was the most frequent, regardless of the period of storage, cementation system, and post-space third. Tag formation was similar among all groups. After 12 months, GC showed the highest bond strength values.